UNA APROXIMACIÓN AL CINE DEL FAN: LAS GRABACIONES CASERAS DE CONCIERTOS POP - Ddo. Cibrán TENREIRO UZAL, (Fonseca, Journal of Communication, 2023)
This article explores the phenomenon of home recordings of pop music concerts as a possible example of a terminological proposal of “fan cinema”. Through the film analysis of numerous concert videos taken from the Internet and films that use it, the text aims to understand if fan identity determines the way fans film, how this relates with visual representations of music nowadays, and if it gives way to recognizable characteristics. In order to it, it also approaches the sample from the perspectives of technological changes (especially those from the digital era),home movies, the role of live spectacles in pop music and fandom theories.